Extract of Yellow Root (Arcangelisia Flava (L.) Merr.) from Several Regions in Kalimantan: Alkaloid Content and Cytotoxicity towards WiDr Colorectal Cancer Cells - Mutiah, Roihatul; Kirana, Farenza Okta; Annisa, Rahmi; Rahmawati, Ana; Sandra, Ferry (Indonesian Society for Cancer Chemoprevention, 2020)
Yellow root (Arcangelisia flava (L.) Merr.) has been scientifically known to have potential as an antimalarial, antibacterial, antioxidant, and anticancer. The purpose of this study was to determine the profile of alkaloid content and cytotoxicity of yellow root extract from several regions in Kalimantan. The alkaloid content was tested using the thin layer chromatography (TLC) method with dragendorf reagent. Cytotoxic in vitro test was conducted against WiDr colorectal cancer cells using the 3-(4,5-dimethylthiazol-2-il)-2,5-diphenyltetrazolium bromide (MTT) assay. Yellow roots were collected from Samarinda city, Banjarmasin city, Barito Timur regency, Malinau district, and Balikpapan City. The MTT inhibitory concentration 50 (IC50) of yellow root extracts were 573.308 μg/mL; 582.857 μg/mL; 296.326 μg/mL; 114.119 μg/mL; and 320.162 μg/mL respectively. Results of the compound identification indicated that alkaloid was found in A. flava from all regions. Alkaloids of A. flava extract should be investigated further in order to find possible active agent that could decrease the viability of WiDr colorectal cancer cells.Keywords: Arcangelisia flava, Borneo, colorectal cancer, Kalimantan, WiDr cells.